Economic and financial viability of the beef sheep farming in the Baixada Cuiabana region (Research, Society and Development, 2022)
This article sought to analyze the economic and financial viability of the production of beef sheep, considering the small properties in the Baixada Cuiabana Citizenship Territory, located in the Midwest region. For the study, only the finishing of the animals for slaughter was considered, with the acquisition of lambs in the region with 30 kg of live weight (kg/BW) and reselling them with 40 kg/BW. The study was carried out through the survey of values ​​referring to initial investments, operational and total costs and revenues, obtained through budgets with suppliers, legislation and the prices practiced in the region. For feasibility analysis, the following profitability and profitability indicators were used: ROI, Operating Margin, Asset/Investment Turnover, EVA, NPV, Payback and IRR, with a minimum attractiveness rate of 8.33% pa, As an investment alternative, the purchase of Treasury Direct bonds, in the pre-fixed modality, is quoted. As a result, the project proved to be unfeasible for the two scenarios presented, with IRR below the minimum rate desired by the entrepreneur and negative NPV.